Informal caregiver burden among stroke survivors in Public Hospital of Selangor, Malaysia: a cross-sectional study - Haron, Zarina; Soh, Kim Lam; Nurul Fatin Atirah, Ahmad Nordin (Penerbit Universiti Putra Malaysia, 2024)
Introduction: Informal caregivers (ICs) play a crucial role in the post-stroke recovery process, contributing significantly to the prevention of complications and functional rehabilitation of stroke survivors. Despite the well-documented stress and challenges faced by caregivers of stroke survivors globally, there is understudied examining the extent of caregiver burden within the specific context of Malaysia. Therefore, this study was to assess the burden level of care among ICs of stroke survivors and its associated factors in the Public Hospital in Selangor, Malaysia. Methods: A cross-sectional study was conducted in the Rehabilitation Clinic and Medical Ward in public hospital in Selangor, Malaysia. A convenience sampling was used that involved 108 ICs who brought stroke survivors to receive their treatment. The caregiver burden was assessed using the Zarit Burden Interview (ZBI) and stroke survivor functional disability was assessed with the Barthel Index. Results: Overall, 60.2% (65) of caregivers experienced a burden, with a high proportion experiencing a mild to moderate burden (45.4%) followed by moderate to severe 13.9% (15). There were statistically significant (r=0.210, p=0.029), a positive association where increasing the age of the ICs may increase the burden to care for the stroke survivor. There were found a significant association between the number of ICs and the level of caregiver burden (p=0.01). Simple linear regression were found functional status of stroke survivors to have significantly (p=0.001) predictor of ICs burden’s level. Conclusion: These findings emphasize the importance of ICs to be included in the rehabilitation planning. Hence, future interventions should be aimed at decreasing ICs burden while simultaneously enhancing the effectiveness of stroke survivor rehabilitation.